2022
DOI: 10.1186/s12916-022-02524-9
|View full text |Cite
|
Sign up to set email alerts
|

A healthy lifestyle is positively associated with mental health and well-being and core markers in ageing

Abstract: Background Studies often evaluate mental health and well-being in association with individual health behaviours although evaluating multiple health behaviours that co-occur in real life may reveal important insights into the overall association. Also, the underlying pathways of how lifestyle might affect our health are still under debate. Here, we studied the mediation of different health behaviours or lifestyle factors on mental health and its effect on core markers of ageing: telomere length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 87 publications
1
20
0
2
Order By: Relevance
“…A large number of factors, such as overweight, gender, changes in health status, physical disabilities, chronic pain, childhood health status, lack of social contact, unhealthy lifestyle and negative event stimulation, were reported to influence the occurrence of depression and anxiety 10–12. Increasing evidence is highlighting the benefits of lifestyle modification in chronic diseases and mental health prevention 12–15. Several systematic reviews and meta-analyses have strengthened the effectiveness of physical activity or daily exercise in managing depression or anxiety 16–18.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of factors, such as overweight, gender, changes in health status, physical disabilities, chronic pain, childhood health status, lack of social contact, unhealthy lifestyle and negative event stimulation, were reported to influence the occurrence of depression and anxiety 10–12. Increasing evidence is highlighting the benefits of lifestyle modification in chronic diseases and mental health prevention 12–15. Several systematic reviews and meta-analyses have strengthened the effectiveness of physical activity or daily exercise in managing depression or anxiety 16–18.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that there are factors such as smoking, drug and alcohol consumption, negative infuences in the social environment, and little education received about sexual relations or emotional intelligence that negatively afect an individual's lifestyle and can prompt violent behaviour. All these causes are variable since they are subject to social and personal factors that can positively or negatively infuence the life of each human being [2].…”
Section: Introductionmentioning
confidence: 99%
“…Because lifestyle factors often co-exist and interact with each other, it is necessary to clarify their combined impact on depression or depressive symptoms. Several studies constructed a healthy lifestyle score and found a bene cial effect of the combination of healthy lifestyles on depression in European [8][9][10][11], Australian [12], and Iranian general adults [13]. A study in French reported a protective association between combined healthy lifestyles and risk of depressive symptoms [14].…”
Section: Introductionmentioning
confidence: 99%